Ovisi li dugoročni gospodarski rast Hrvatske o demografiji ili ipak proizvodnosti? - Lovrinčević, Željko (Array, 2019)
The aim of this paper is to provide long-term projections of economic growth in the Republic of Croatia for the period up to 2050. Long-term projections of the economic growth are useful tool for identification of potential growth limitations related to different socioeconomic issues: demography, fiscal sustainability, environmental protection and many other aspects. The projections are based on Cobb-Douglas’s type of production function in order to be comparable to European Commission long-term projections for all member states. Expected long-term economic developments are based on demographic projections, as well as projections of capital deepening and total factor productivity growth. Long-term projections are faced to many uncertainties, especially path of total factor productivity path in the long run. Research results point to the increase of investment efficiency and total factor productivity growth as the most important drivers for long-term growth. In addition, labor market participation rate seems to be of utmost importance. This could, at least to some extent, mitigate negative demographic trends and further working-age population shrinking. Long-term projections are usually faced to a high level of uncertainty. Many variables are exposed to future changes in alternative scenarios. The results and conclusions presented in this paper fill the gap in domestic literature on the long term potential growth in the Republic of Croatia. The alternative scenarios of growth could serve as a basis for a number of strategic documents dealing with energy, regional policy, industry, demographic, health, and environmental protection issues. The research results suggest that the average annual economic growth rate in Croatia up to 2050 in Croatia would be in range of 1.1 percent (base scenario) up to 1.9 percent, depending on the growth rate of total factor productivity.